Faktor-faktor Risiko Fiskal dalam Penganggaran Daerah Daerah - Arina Romarina; Akhmad Makhfatih (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2010)
Fiscal risk refers to the chance that some unfavorable event will occur in fiscal term. It also influences the implementation of Anggaran Pendapatan dan Belanja Negara (APBN) and Anggaran Pendapatan dan Belanja Daerah (APBD) The impact of fiscal risk is on the accuracy of government financial target or imbalanced financial budgeting. The aim of this research is to identify and analyze the fiscal risk factors in local financial budgeting. Quantitative and qualitative methods are used in this research where confirmatory factor analysis is used as analitical tools. The primary data is collected from 125 respondents who are civil servant. The qualification of the respondent is the civil servant who has been ever involve in arranging local budget. The results show that there are many fiscal risk factors in local budgeting. These factors involve both external and internal aspects such as synchronization of APBD with Kebijakan Umum Anggaran (KUA) and Prioritas Plafon Anggaran Sementara (PPAS), risk management, accessibilty and transparancy, target and performance indicators, legislative and executive relations, opportunistic behaviour, moral hazard, organization management, risk anticipation, the pattern of financial planning, the financial planning lag approval, the unwritten expenses and macroeconomics conditions.